Health-related quality of life in syndromic scoliosis treated by segmental pedicle screw instrumentation: a case-control study - Sallinen, Henri; Saarinen, Antti; Raitio, Arimatias; Ahonen, Matti; Helenius, Ilkka (MJS Publishing, Medical Journals Sweden AB, 2026)
Background and purpose: Deformity correction with pedicle screw instrumentation in adolescent idiopathic scoliosis has been shown to improve the health-related quality of life (HRQoL), while evidence on syndromic scoliosis is limited. Syndromic patients tend to have comorbidities resulting in a higher risk of perioperative complications. We aimed to assess the change in HRQoL in patients with syndromic scoliosis compared with adolescent idiopathic scoliosis after spinal fusion with pedicle screw instrumentation.
Methods: We conducted a retrospective case-control study in children undergoing segmental pedicle screw instrumentation for syndromic scoliosis between 2009 and 2023 with a 2-year follow-up. For each syndromic patient, 2 controls with adolescent idiopathic scoliosis were matched for sex and age. The Scoliosis Research Society-24 (SRS-24) questionnaire was used to assess HRQoL preoperatively and at follow-up.
Results: 35 syndromic (mean age 14.1 years) and 70 adolescent idiopathic patients (mean age 15.1 years) were included. The SRS-24 total score remained stable from preoperative to 2-year follow-up in both groups (median difference for change 0.05, 95% confidence interval [CI] -0.40 to 0.30). The pain domain improved 0.9 points (standard deviation [SD] 0.9) in syndromic and 1.0 points (SD 0.7) in adolescent idiopathic scoliosis patients. Non-ambulatory patients had greater improvement in pain than ambulatory syndromic patients (mean difference between groups 0.66, CI 0.15-1.24). 8 syndromic patients had complications compared with 3 adolescent idiopathic scoliosis patients (risk ratio 5.3, CI 1.5-19). One syndromic patient died during follow-up.
Conclusion: The health-related quality of life in patients with syndromic scoliosis was comparable to patients with adolescent idiopathic scoliosis after posterior spinal fusion with segmental pedicle screw instrumentation.